1997
DOI: 10.1021/bc9700852
|View full text |Cite
|
Sign up to set email alerts
|

Biotin Reagents for Antibody Pretargeting. Synthesis, Radioiodination, and in Vitro Evaluation of Water Soluble, Biotinidase Resistant Biotin Derivatives

Abstract: As part of our development of antibody pretargeting for cancer therapy, an investigation has been conducted to examine the stability of water solubilized, radioiodinated biotin derivatives toward biotinidase degradation in mouse and human serum. Eight new biotin derivatives were synthesized to conduct the study. The biotin derivatives synthesized contained (1) the biotin moiety, (2) a water solubilizing linker moiety, (3) p-iodobenzoate or p-tri-n-butylstannylbenzoate moieties, and (4) in some of the compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
97
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(99 citation statements)
references
References 29 publications
2
97
0
Order By: Relevance
“…Finally, the biotin-tag was protected from serum biotinidase activity by incorporation of 2-aminobutyric acid (27,30 ) to avoid the use of iodacetamid, which inhibits not only biotinidase but also cysteine proteases (31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the biotin-tag was protected from serum biotinidase activity by incorporation of 2-aminobutyric acid (27,30 ) to avoid the use of iodacetamid, which inhibits not only biotinidase but also cysteine proteases (31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Reduced eYcacy of tumor imaging and therapy techniques that utilize unstable biotin labels has also been a concern of others [1,2,12,13,15]. In a previous study, we directly demonstrated that a variety of commercially available biotinylating agents produced biotin labels that are cleaved in the presence of plasma [4].…”
Section: Discussionmentioning
confidence: 97%
“…Wilbur et al [3] speculated that the loss of binding to (strept)avidin is the action of biotinidase cleavage of biotin from the Fab' and noted that other investigators had reported the need to develop metabolically stable biotin conjugates. Indeed, Wilbur et al published a series of papers describing modiWcations of the biotinamide bond to protect bond stability and retain aqueous solubility without aVecting binding to (strept)avidin [1,[12][13][14][15]. In many of these reports, biotinidase is inferred, although not directly shown, to catalyze the cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of the studies was the investigation of antibody conjugates with recombinant streptavidin in tumor pretargeting protocols, a method for amplifying the amount of radioactivity delivered to cancer cells. [8] Many derivatives have been synthesized by Wilbur and coworkers containing two and three biotin moieties with varying distances between the carbon atoms of the biotin amide. [9] Only tris-biotinylated compounds completely polymerized in SAv solution and similar results were obtained in the surface-bound SAv cross-linking experiment.…”
mentioning
confidence: 99%
“…[8,17] Since the relaxivity of the Gd 3 L2/Av adduct is more than two times higher than the relaxivity of free Gd 3 L2, the degradation of the adduct can be followed by measuring the proton relaxation rate (R 1obs ) of the solution. For this purpose, the R 1obs of solutions containing Gd 3 L2/Av (0.5 mm protein concentration) were measured after dilution 1:10 with human serum.…”
mentioning
confidence: 99%